2013
DOI: 10.1002/lt.23618
|View full text |Cite
|
Sign up to set email alerts
|

Increased morbidity in overweight and obese liver transplant recipients: A single-center experience of 1325 patients from the United Kingdom

Abstract: Obesity levels in the United Kingdom have risen over the years. Studies from the United States and elsewhere have reported variable outcomes for obese liver transplant recipients in terms of post-liver transplant morbidity, mortality, and graft survival. ). The primary outcome was an evaluation of graft and patient survival, and the secondary outcome was an assessment of postoperative morbidity. Bonferroni correction was applied with statistical significance set at P < 0.012. Kaplan-Meier curves were used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 32 publications
5
101
1
4
Order By: Relevance
“…Nair et al [22] analyzed the UNOS database on 18172 LT patients transplanted between 1988 and 1996 and found that primary graft dysfunction, perioperative mortality at 1, 2, and 5-years were significantly higher in the morbidly obese group due to cardiovascular adverse events. Similar outcomes were reported in 1325 obese LT recipients [27] from the United Kingdom where they had increased morbidity due to infectious complications, longer ICU and hospital stay in comparison to normal weight patients. However, other studies suggested that higher BMI should not be considered an absolute contraindication to LT [24,28] .…”
Section: Before Transplantsupporting
confidence: 74%
“…Nair et al [22] analyzed the UNOS database on 18172 LT patients transplanted between 1988 and 1996 and found that primary graft dysfunction, perioperative mortality at 1, 2, and 5-years were significantly higher in the morbidly obese group due to cardiovascular adverse events. Similar outcomes were reported in 1325 obese LT recipients [27] from the United Kingdom where they had increased morbidity due to infectious complications, longer ICU and hospital stay in comparison to normal weight patients. However, other studies suggested that higher BMI should not be considered an absolute contraindication to LT [24,28] .…”
Section: Before Transplantsupporting
confidence: 74%
“…However, studies have suggested higher morbidity in the early post-transplant setting and longer length of stay in patients that are morbidly obese [2,3]. This study by Singhal et al, supports these findings, but provides some granularity into why the postoperative complications may be more frequent and length of stay may be longer.…”
supporting
confidence: 76%
“…Alternatively, the obese patients may have had biliary complications that were less severe and more amenable to nonsurgical therapies. Although rates of postoperative respiratory infections were similar between the 2 groups, 38 postoperative respiratory failure occurred more commonly among obese versus nonobese recipients (23% vs 3%; P = 0.009). 32 …”
Section: Peritransplant Considerationsmentioning
confidence: 82%
“…31,38,40,41 In the largest single-center cohort that included a total of 1325 LT recipients from 1994 to 2009, both ICU LOS (4.7 vs 3.2 days; P = 0.03) and total hospital LOS (22.4 vs 18.0 days; P = 0.047) were significantly higher among the 73 recipients with BMI of 35 or greater compared with the 643 recipients with BMI of 18.5 to 24.9. 38 These findings were confirmed in an analysis of the Scientific Registry of Transplant Recipients (SRTR) data. Among 12 445 LT recipients, 416 (3%) of whom had a BMI of 40 or greater (class III obesity) ICU days (mean [SD], 3 [6] vs 3 [4]; P < 0.001) and hospital days (11 [10] vs 9 [8]; P < 0.001) were both significantly higher in recipients with a BMI of 40 or greater compared with those with a BMI less than 40.…”
Section: Peritransplant Considerationsmentioning
confidence: 99%